Mechanical behavior of conceptual posterior dental crowns with functional elasticity gradient - Penteado, Marcela Moreira [UNESP]; Tribst, Joao Paulo Mendes [UNESP]; De Oliveira Dal Piva, Amanda Maria [UNESP]; Ausiello, Pietro; Zarone, Fernando; Garcia-Godoy, Franklin; Borges, Alexandre Luiz Souto [UNESP] (My University, 2019)
Purpose: To evaluate the biomechanical behavior of monolithic ceramic crowns with functional elasticity gradient. Methods: Using a CAD software, a lower molar received a full-crown preparation (1.5 mm occlusal and axial reduction). The monolithic crown was modeled with a resin cement layer of 0.1 mm. Four groups were distributed according to the full crown elastic modulus (E):(a) Bioinspired crown with decreasing elastic modulus (from 90 to 30GPa); (b) Crown with increasing elastic modulus (from 30 to 90 GPa); (c) Rigid crown (90 GPa) and (d) Flexible crown (30 GPa). The model was exported to the analysis software and meshed into 385.240 tetrahedral elements and 696.310 nodes. Materials were considered isotropic, linearly elastic, and homogeneous, with ideal contacts. A 300-N load was applied at the occlusal surface and the base of the model was fixed in all directions. The results were required in maximum principal stress criterion. Results: Crowns consisting of layers with increasing elastic modulus presented intermediate results between the rigid and flexible crowns. Compared to the flexible crown, the bioinspired crown showed acceptable stress distribution across the structure with lower stress concentration in the tooth. In dental crowns the multilayer structure with functional elasticity gradient modifies the stress distribution in the restoration, with promising results for bioinspired design.